Unlocking words and fluency: Spaced Retrieval small-scale case study practice with Spanish-speaking A1 EFL adult learners - Dávila-Bajaña, Tiffany; Salas-Vaca, Lizeth; Sánchez-Valdiviezo, Penélope; Contreras-Falcones, Alexis; Faytong-Haro, Marco (Frontiers in Education, 2026)
This small-scale case study explores the impact of Spaced Retrieval Practice (SRP) on vocabulary acquisition and oral fluency in Spanish-speaking A1 EFL adult learners, addressing the need for effective instructional strategies that enhance long-term retention and fluency development. Given the importance of lexical knowledge in oral proficiency, this research aims to determine the extent to which SRP influences Mean Length of Run (MLR), Articulation Rate (AR), and Target Vocabulary Usage. A quasi-experimental design was implemented with eight adult learners enrolled in an A1-level English course. Participants completed a pretest and posttest, during which their oral responses were recorded and analyzed using PRAAT software to measure MLR and AR. Target Vocabulary Usage was also calculated through percentage comparisons. The results indicate that MLR and AR increased significantly (p = 0.015), suggesting that learners were able to sustain speech for longer stretches. Additionally, Target Vocabulary Usage increased, demonstrating a positive trend in lexical recall even though this change was not statistically significant (p = 0.117). A correlation was observed between Target Vocabulary Usage and MLR gains suggesting that Spaced Retrieval Practice likely enhanced vocabulary retention and contributed to oral fluency development, supporting its integration into EFL curricula as a pedagogical strategy for improving speaking skills. Further research is recommended to explore longer interventions and digital retrieval tools.